Peran Profitabilitas Dalam Memoderasi Tax Avoidance: Dilihat dari Ukuran Perusahaan Pertambangan di Indonesia - Oktafiyani, Melati; Permana, Cahya Bagus (Jurusan Akuntansi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Pekalongan, 2021)
Tax avoidance is an action designed to reduce the amount of tax required by the corporation. However, the agency theory is that opportunistic managers may reduce tax obligations through complex transactions, allowing them to evade or pursue their own interests. Hence, the need to examine the relationship between firm size, profitability, and tax avoidance is evident. This study aims to assess empirical relationships using a sample of mining listed companies in IDX over the period 2014 to 2019, using moderated regression analysis. The findings indicate that firm size affects the tax avoidance, but this relationship is not moderated by profitability.